microRNA-130b downregulation potentiates chondrogenic differentiation of bone marrow mesenchymal stem cells by targeting SOX9 - Zhang,Penggui (2021)
Osteoarthritis (OA) is a chronic health condition. MicroRNAs (miRs) are critical in chondrocyte apoptosis in OA. We aimed to investigate the mechanism of miR-130b in OA progression. Bone marrow mesenchymal stem cells (BMSCs) and chondrocytes were first extracted. Chondrogenic differentiation of BMSCs was carried out and verified. Chondrocytes were stimulated with interleukin (IL)-1β to imitate OA condition in vitro. The effect of miR-130b on the viability, inflammation, apoptosis, and extracellular matrix of OA chondrocytes was studied. The target gene of miR-130b was predicted and verified. Rescue experiments were performed to further study the underlying downstream mechanism of miR-130b in OA. miR-130b first increased and drastically reduced during chondrogenic differentiation of BMSCs and in OA chondrocytes, respectively, while IL-1β stimulation resulted in increased miR-130b expression in chondrocytes. miR-130b inhibitor promoted chondrogenic differentiation of BMSCs and chondrocyte growth and inhibited the levels of inflammatory factors. miR-130b targeted SOX9. Overexpression of SOX9 facilitated BMSC chondrogenic differentiation and chondrocyte growth, while siRNA-SOX9 contributed to the opposite trends. Silencing of SOX9 significantly attenuated the pro-chondrogenic effects of miR-130b inhibitor on BMSCs. Overall, miR-130b inhibitor induced chondrogenic differentiation of BMSCs and chondrocyte growth by targeting SOX9.